PERAN SATUAN PENDIDIKAN DALAM PENGUATAN ETIKA PROFESI GURU DI ERA DIGITAL: KEBIJAKAN, BUDAYA & TATA KELOLA - Azzah Naili Falakhiyah; Dina Fika Ariyani; Nanda Nayla Nabila; Muhlisin (Educational Research Center, 2026)
The development of the digital era in the world of education presents opportunities for learning innovation as well as challenges to the professionalism and work ethics of teachers, especially regarding integrity, accountability, and ethics in digital interactions. This study aims to analyze the role of educational institutions in strengthening the professional ethics of teachers through aspects of policy, school culture, and educational management. The study used a qualitative approach with the Systematic Literature Review (SLR) method based on library studies of scientific journals, with data collection techniques through documentation and content analysis. The results of the study indicate that strengthening the professional ethics of teachers can be done through the integration of codes of ethics in school policies, academic supervision, professional training, strengthening digital ethics, establishing a school culture oriented towards integrity and responsibility, and educational management that applies the principles of accountability, transparency, participation, and performance-based supervision.